Effect of Adding Vitamin to Cooking Oil on Peroxide Value - Hanoun, Zainab Majid Khalid; Yaseen, Ibtihal Ali Hassan; Dhaya’a, Ikhlas Fahem Sahib; Sultan, Huda Slman Falih; Abdul Ali Dakhel, Riyam Saadoun; Hamza, Zahraa Hadi Mohammed (American Journal of Biomedicine and Pharmacy, 2025)
The aim of this research is to reduce the number of peroxides in two frying oil samples by using one of the natural antioxidants which is vitamin E, one of the chemical specifications that assess the oil is the peroxide number, which is the amount of free radicals formed in the oil and the number of peroxides increases during exposure to heat, moisture, oxygen, bad storage conditions, light or other conditions. These peroxides have a harmful effect on the consumer health (Carcinogenic substances). The vitamin E had a clear impact on the peroxide value, as when conducting the experiment and using oil to fry potato slices, the number of peroxide was high before adding vitamin E which score approximately (Peroxide number is 5.6 for 15 minutes, 9.8 for 30 minutes, and 11.6 for 45 minutes). After using vitamin E in amount of 10 microgram per 100 ml of oil, the effect was clear of vitamin E on the number of peroxide as it decreased significantly. Which scored (5 for 15 minutes, 8.1 for 30 minutes, 8.9 for 45 minutes), When vitamin E added by 20 microgram the result was (4.8 for 15 minutes, 5.5 for 30 minutes, 6.5 for 45 minutes). 50 micrograms per 100 oil shown to have no significant effect on the peroxide value. it was found that the best concentration is 20 microgram for a sample of 100 ml of oil .